A simple risk index predicts endovascular treatment outcomes in acute ischemic stroke: prognostic value of SPAN-100 - Noémie Ligot; Marie Dagonnier; Boris Lubicz; Nicolas Brassart; Gilles Naeije (Frontiers in Neurology)
BackgroundMechanical thrombectomy (MT) is a proven intervention for patients with acute ischemic stroke (AIS) due to a large vessel occlusion (LVO). However, outcomes after MT remain variable, particularly in high-risk groups. The SPAN-100 index, a simple bedside tool combining age and baseline NIHSS scores, has been associated with poor outcomes in AIS patients treated with intravenous thrombolysis. This study evaluates the prognostic value of the SPAN-100 index and its weighted variant (wSPAN) in predicting outcomes following MT.MethodsWe conducted a retrospective cohort study of patients with AIS who were treated with MT between 2015 and 2024 at two Belgian university hospitals. SPAN and wSPAN scores were calculated at admission, and patients were stratified by SPAN ≥100 vs. <100. The primary outcome was functional status at 90 days, as assessed using the modified Rankin Scale (mRS). Secondary outcomes included mortality (mRS = 6) and favorable outcomes (mRS ≤ 3). Discriminative ability was assessed using receiver operating characteristic (ROC) analysis (AUC, 95% CI), and model performance was evaluated using AIC and BIC. The positive predictive value (PPV) and negative predictive value (NPV) were calculated for SPAN ≥100, and outcome proportions were compared between SPAN-defined groups using Fisher’s exact test.ResultsA total of 530 patients were included, of whom 116 had SPAN scores of ≥100. These patients experienced significantly worse outcomes, with higher mortality (60.0% vs. 17.6%) and lower rates of mRS ≤ 3 (19.2% vs. 71.6%, both p-values < 0.001). However, among survivors with SPAN scores of ≥100, nearly half of them achieved recovery (mRS ≤ 3). ROC analysis showed good discrimination for both SPAN and wSPAN: AUCs were 0.77 and 0.78 for mRS ≤ 3 and 0.80 and 0.81 for mortality. wSPAN showed a slightly better model fit (lower AIC/BIC). The SPAN ≥100 threshold had a high PPV for poor outcomes and a high NPV for survival.ConclusionSPAN-100 and wSPAN are pragmatic and reliable prognostic tools for AIS patients undergoing MT. While a SPAN score ≥100 identifies a high-risk group with poorer overall outcomes, it should not be used as an exclusion criterion. Many patients with a SPAN score ≥100 achieved functional recovery, supporting MT as a justified intervention even for older, more severely affected individuals. These findings highlight the importance of combining risk stratification with clinical judgment rather than relying on rigid thresholds.